(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
In recent times, capital markets have become global and continue to expand. Moreover, there has been significant globalization of production and trade. Investors can trade shares and securities worldwide. Entities are in a position to access the funds globally in the most advantageous markets.